The high, hidden social and environmental costs of food in Kenya - International Food Policy Research Institute (International Food Policy Research Institute, 2024)
Food costs usually encompass prices consumers pay and investments in production and transportation. But the hidden costs of food - including forced labor, underpaid labor and environmental damage - are typically not on the food bill. New research shows the extent of the hidden costs of food in Kenya.